A step-up action-research model for the revitalisation of service learning modules - Ielse Seale; Annette Wilkinson; Mabel Erasmus (Acta Academica, 2005)
This reflective overview indicates how action research was utilised to revitalise and improve service learning modules for first-year nursing students at the University of the Free State. The two modules under consideration include a curriculum-based community development project in which the students compile a community profile and subsequently strive to address identified needs and challenges together with the community. A step-up action-research model was developed to enhance the quality of these service learning modules, mainly by focusing on a more thorough integration of service, learning and research, with this finally resulting in more sustainable student learning and community development. The research process has moreover demonstrated the importance and appropriateness of action research for the development of higher education service learning modules.